The Relationship between VDR Gene Polymorphisms Bsm1 and Apa1 with Breast Cancer Risk - Mozaffarizadeh, Hengameh; Mokarian, Fariborz; Salehi, Mansoor; Hakimian, Seyyed Mohammad Reza; Moazam, Elham; Amoozadehsamakoosh, Amirmohammad; Hosseinzadeh, Majid; Behnam, Mahdieh; Behjati, Mohaddeseh; Naseri, Alma; Lotfi, Marzieh; Tohidi, Fatemeh (Global Medical Genetics, 2024)
Background In addition to its multifaceted physiological functions, vitamin D is recognized for its protective role against cancer. To manifest its effects, vitamin D engages with the vitamin D receptor (VDR) gene responsible for its encoding. Investigations have unveiled that polymorphisms within the VDR gene exert influence over the expression and/or functionality of the VDR protein. Notably, certain VDR gene polymorphisms have emerged as particularly pertinent in the context of tumorigenesis, including Fok1 (rs2228570), Bsm1 (rs1544410), Taq1 (rs771236), and Apa1 (rs7975232). This study aims to scrutinize the correlation between the Bsm1 and Apa1 polymorphisms and the susceptibility to breast cancer development.Materials and Methods In this study, 50 patients suffering from breast cancer with less than 6 months breast cancer diagnosis and 50 healthy control individuals have been chosen. Restriction fragment length polymorphism polymerase chain reaction was used to determine the genotype of polymorphisms.Results The results of the statistical analysis showed that among the studied polymorphisms, there was no correlation with the development of breast cancer.Conclusion Studies on various cancers have produced inconsistent results regarding vitamin D's role in the development and progression of cancer. Therefore, further research is necessary to determine vitamin D's role in cancer development and progression.
Keywords: breast cancer; VDR gene; polymorphism